Efektywność ekonomiczna przedsiębiorstw rolnych jako podstawowe kryterium ich konkurencyjności - Siekierski, Jan (Economic Effectiveness of Agricultural Enterprises as a Basic Criterion of Their Competitiveness, 2006)
The assessment of economic effectiveness of 300 large area agricultural enterprises investigate by the Institute of Agricultural Economics and Food Economy (IERiGŻ) is assumed as the basic criterion for competitiveness. The analysis also refers to sectors with various forms of property management and directions of production.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 299-306